2015
DOI: 10.13073/fpj-d-14-00056
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Decay and Termite Resistance of Western Red Cedar Heartwood

Abstract: Western red cedar (WRC; Thuja plicata) is highly valued for its natural durability. Rapid methods to assess heartwood durability are needed to identify breeding stock that will ultimately yield trees with durable wood when harvested. Chromatographic methods to detect heartwood extractives have been developed, but these still require significant time and laboratory resources and rely upon an understanding of the relationship between extractives and durability that is still incomplete. Visible/near-infrared (VIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Decay resistance also varies within the stem e.g. it tends to increase radially from pith to the heartwood-sapwood boundary and longitudinally from crown to base (Stirling et al 2015), and is typically connected to the wood chemical composition, in particular, with the extractives present (Daniels and Russell 2007, Gierlinger et al 2003, Pâques and Charpentier 2015. Nevertheless, the reasons of resistance to decay may not be directly translated into resistance to insect attacks: for instance, Taylor et al (2006) found that the total wood extractives amount was important but alone could not explain termite durability in Thuja plicata and Chamaecyparis nootkatensis, and Stirling et al (2015) confirmed the findings for Thuja plicata.…”
Section: Introductionmentioning
confidence: 99%
“…Decay resistance also varies within the stem e.g. it tends to increase radially from pith to the heartwood-sapwood boundary and longitudinally from crown to base (Stirling et al 2015), and is typically connected to the wood chemical composition, in particular, with the extractives present (Daniels and Russell 2007, Gierlinger et al 2003, Pâques and Charpentier 2015. Nevertheless, the reasons of resistance to decay may not be directly translated into resistance to insect attacks: for instance, Taylor et al (2006) found that the total wood extractives amount was important but alone could not explain termite durability in Thuja plicata and Chamaecyparis nootkatensis, and Stirling et al (2015) confirmed the findings for Thuja plicata.…”
Section: Introductionmentioning
confidence: 99%
“…observed in the study. Stirling et al (2015) reported similar outcome on Coptotermes formosanus Shiraki mortality and damage caused on Western Red Cedar Heartwood (Thuja plicata L.).…”
Section: Discussionmentioning
confidence: 67%